2005
DOI: 10.1007/s00335-004-2447-4
|View full text |Cite
|
Sign up to set email alerts
|

On growth, fatness, and form: A further look at porcine Chromosome 4 in an Iberian × Landrace cross

Abstract: A crossed population between Iberian x Landrace pigs consisting of 321 F2, 87 F3, and 85 backcross individuals has been analyzed to refine the number and positions of quantitative trait loci (QTL) affecting shape, growth, fatness, and meat quality traits in SSC4. A multitrait multi-QTL approach has been used. Our results suggest that carcass length and shoulder weight are affected by two loci. The first one, close to the AFABP gene, has a very strong pleiotropic effect on fatness, whereas the second one, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…9,10,22,65,87). Moreover, the most significant QTL detected in this study, i.e., the QTL for TG190 on SSC4, coincides with a QTL for backfat thickness, the FAT1 locus, that has been reported in many unrelated pig crosses and populations (5,10,39,47). Consistent with these facts, significant positive correlations were found in our Duroc population between cholesterol measures at 190 days and other fatness and morphological traits, specifically backfat thickness (correlation coefficients from 0.27 to 0.34) and live weight (correlation coefficients between 0.18 and 0.23), but no significant correlations were found with TG levels.…”
Section: Serum Lipid Qtl In Pigsmentioning
confidence: 81%
See 1 more Smart Citation
“…9,10,22,65,87). Moreover, the most significant QTL detected in this study, i.e., the QTL for TG190 on SSC4, coincides with a QTL for backfat thickness, the FAT1 locus, that has been reported in many unrelated pig crosses and populations (5,10,39,47). Consistent with these facts, significant positive correlations were found in our Duroc population between cholesterol measures at 190 days and other fatness and morphological traits, specifically backfat thickness (correlation coefficients from 0.27 to 0.34) and live weight (correlation coefficients between 0.18 and 0.23), but no significant correlations were found with TG levels.…”
Section: Serum Lipid Qtl In Pigsmentioning
confidence: 81%
“…In this way, knockout mice for ABCG5 and ABCG8 show an enhanced intestinal absorption of CT (32). We would like to highlight the SSC4 QTL for TG190, which maps to the FAT1 locus influencing backfat thickness, reported in several pig populations (5,10,39,47,53). The CI of this QTL coincides with the location of genes encoding fatty acid binding proteins 4 and 5 (FABP4 and FABP5;Ref.…”
Section: Serum Lipid Qtl In Pigsmentioning
confidence: 99%
“…The results are even more surprising when one considers that a highly significant QTL (P , 10 À10 ) affecting fatness maps very close to the FABP4 region (Mercade et al 2005). At first glance, a selective sweep promoted by a hitchhiking event acting on a beneficial mutation (i.e., directional selection) or a bottleneck event caused by domestication might generate the observed unusual haplotype structure with two characteristic clades (clades A and B, Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Yet its precise molecular nature has remained elusive so far. Recently, we have shown in an Iberian 3 Landrace cross that the FAT1 region is made up of at least two loci, with FABP4 being a very good positional candidate for one of them (Mercade et al 2005(Mercade et al , 2006. In addition, several studies have demonstrated that FABP4 plays a critical role in fatty acid uptake and metabolism.…”
mentioning
confidence: 99%
“…Most of the multi-trait QTL mapping approaches model the genetic (co)variances by an unstructured model (Jiang and Zeng 1995;Korol et al 1998;Knott and Haley 2000;Hackett et al 2001;Lund et al 2003), which in practice limits the number of traits that can be handled. It is symptomatic that the applications of multi-trait QTL mapping under the use of unstructured (co)variance matrices never included more than just a few traits, i.e., mostly 2-5 (Calinski et al 2000;Hackett et al 2001;Szyda et al 2003;Mercadé et al 2005;Olsen et al 2005). With few traits and/or environments, the unstructured model is a possible option, although not necessarily the optimal one.…”
Section: Discussionmentioning
confidence: 99%